Molecular Monitoring of Succession of Bacterial Communities in Human Neonates - Favier, Christine F. (American Society for Microbiology, 2002)
The establishment of bacterial communities in two healthy babies was examined for more than the first 10 months of life by monitoring 16S ribosomal DNA (rDNA) diversity in fecal samples by PCR and denaturing gradient gel electrophoresis (DGGE) and by analyzing the sequences of the major ribotypes. DGGE profiles of the dominant populations in the intestines of the infants were obtained by analyzing daily or weekly fecal samples. After delivery, the germfree infant gastrointestinal tracts were rapidly colonized, and the succession of bacteria in each ecosystem was monitored. During the first few days of life the profiles were simple, but they became more complex as the bacterial diversity increased with time in both babies. Clone libraries of amplified 16S rDNA fragments from baby feces were constructed, and these libraries allowed identification of the bacterial types by comparative DNA sequence analysis; the bacteria identified included members of the genera Bifidobacterium, Ruminococcus, Enterococcus, Clostridium, and Enterobacter. Species most closely related to the genera Bifidobacterium and Ruminococcus in particular dominated the intestinal microbiota based on the stability over time and the numbers, as estimated by the intensities of the bands. However, 19 of the 34 cloned rDNA sequences exhibited less than 97% identity with sequences of known bacteria or cloned sequences in databases. This study showed that using PCR-DGGE and 16S rDNA sequence analysis together resulted in a dynamic description of bacterial colonization in the infant intestinal ecosystem and allowed visualization of bacteria that are difficult to cultivate or to detect by other methods.